2022
DOI: 10.2147/cia.s346954
|View full text |Cite
|
Sign up to set email alerts
|

White-Cell Derived Inflammatory Biomarkers in Prediction of Postoperative Delirium in Elderly Patients Undergoing Surgery for Lower Limb Fracture Under Non-General Anaesthesia

Abstract: Purpose The aim of this study was to investigate whether white-cell derived biomarkers could serve as potential markers in prediction of postoperative delirium (POD) after lower limb fracture. Patients and Methods Elderly patients with surgery for lower limb fracture under non-general anaesthesia were included. Neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and platelet-to-white cell ratio (PWR), which were most recently measured preceding surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…High clinical significance can result from the identification of predictive biomarkers that allow for early risk stratification of hip fracture patients who are vulnerable to POD. The incidence and severity of POD in hip fracture patients were associated with higher levels of white blood cells, neutrophil/lymphocyte ratio, neutrophil percentage, and lower levels of mean platelet volume and basophil percentage ( Thisayakorn et al, 2021 ; Li et al, 2022 ), which further demonstrated that immune-inflammatory processes are involved in the pathophysiology of POD. Prognostic Nutritional Index (PNI) is a convenient and accurate way to quantify nutritional status, and it was calculated as 10 × albumins (g/dl) + 0.005 × total lymphocyte count (per mm 3 ; Onodera et al, 1984 ).…”
Section: Pathophysiological Changesmentioning
confidence: 89%
“…High clinical significance can result from the identification of predictive biomarkers that allow for early risk stratification of hip fracture patients who are vulnerable to POD. The incidence and severity of POD in hip fracture patients were associated with higher levels of white blood cells, neutrophil/lymphocyte ratio, neutrophil percentage, and lower levels of mean platelet volume and basophil percentage ( Thisayakorn et al, 2021 ; Li et al, 2022 ), which further demonstrated that immune-inflammatory processes are involved in the pathophysiology of POD. Prognostic Nutritional Index (PNI) is a convenient and accurate way to quantify nutritional status, and it was calculated as 10 × albumins (g/dl) + 0.005 × total lymphocyte count (per mm 3 ; Onodera et al, 1984 ).…”
Section: Pathophysiological Changesmentioning
confidence: 89%
“…This change in peripheral circulation may involve disrupting the blood-brain-barrier and microglia, which activates and releases cerebral cytokines, resulting in POD [22,24]. Second, many studies have found that white-cell derived inflammatory markers, such as the NLR, PLR, and PWR, are associated with delirium [11][12][13][14][15]. As one of the white-cell derived inflammatory markers, the SII was also calculated using neutrophil, lymphocyte, and platelet counts.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with IL-6, IL-8, C-reactive protein, and S-100β, white-cell derived inflammatory biomarkers, namely, the neutrophil-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), platelet-to-white cell ratio (PWR), and systemic immune inflammation index (SII, platelet × neutrophil/lymphocyte), can be obtained for a lower cost and require less time. Some studies have shown the potential value of the NLR, PLR, and PWR in predicting POD after lower limb, head and neck free-flap reconstruction, total hip arthroplasty, abdominal surgery, oesophagectomy carotid endarterectomy, and cardiac surgery [11][12][13][14][15]. As a white-cell derived inflammatory biomarker, systemic immune inflammation index (SII) has been used to predict ischemic stroke, delayed vasospasm, microvascular dysfunction, and acute kidney injury [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies noted that neuroinflammation might have a crucial effect on the progression of POD, and neutrophils and lymphocytes were the major effectors of neuroinflammation among elderly patients with delirium, manifested as increased neutrophil count and decreased lymphocyte count (Kotfis et al, 2019;Oh & Park, 2019). As studies mentioned, a high level of NLR has been identified as an independent risk factor for POD in acute ischemic stroke and orthopedic surgery (Guldolf et al, 2021;Li et al, 2022). Also, other inflammatory markers ratios, such as MLR and PLR, played a prominent role in predicting POD after cardiac surgery ( Şaşkin et al, 2022;Su et al, 2022).…”
Section: Discussionmentioning
confidence: 99%